Profiles and determinants of Nigeria's balance of payments: the current account component, 1950-88 - Umo, Joe U.; Fakiyesi, Tayo. (Nairobi : African Economic Research Consortium, 1995)
This research paper examine the economic crisis since the beginning of the 1980s. it further highlights problem associated with the Nigeria balance of payments.
"November, 1995."
Includes bibliographical references (p. [57]-59).
asm; 27/02/19
Loans
Keywords: Balance of payments; Trade; Current account; Nigeria